2012
DOI: 10.1111/j.1753-6405.2012.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of chronic physical health disorders in Australians with diagnosed mental illness

Abstract: Objective: To compare chronic physical health disorder prevalence amongst Australian adults with and without mental illness. Method: Total n=1,716 participants (58% female) with a mean age of 52 ± 13 years (range: 18 to 89 years) completed an online survey of Australian adults in 2010. Outcome measures including prevalence of chronic physical conditions and self‐reported body mass index (BMI) in n=387 (23%) with a self‐reported mental illness diagnosis were compared to respondents without mental illness. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Research indicates that people diagnosed with a mental disorder are more likely to smoke, and have more than a two-fold increased risk of chronic diseases compared to the general population (HSCIC, 201;McManus, Meltzer & Campion, 2010;RCP, 2013;Ruther, et al, 2014;Scott et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that people diagnosed with a mental disorder are more likely to smoke, and have more than a two-fold increased risk of chronic diseases compared to the general population (HSCIC, 201;McManus, Meltzer & Campion, 2010;RCP, 2013;Ruther, et al, 2014;Scott et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Either as a consequence of, or in addition to the potential side effects of medication, people with SMI are considerably more likely to exhibit comorbid physical illness compared to those without mental illness (De Hert et al, 2011;Hardy & Thomas, 2012;Scott et al, 2012). This partly explains the two to threefold increase in mortality risk experienced in this population, with the most common cause of mortality being treatable physical illnesses such as cardiovascular disease (Brown, Kim, Mitchell & Inskip, 2010).…”
mentioning
confidence: 97%
“…7 This increased prevalence of noncommunicable diseases is likely to be partially explained by increased prevalence of poor health behaviors. Accordingly, this populationbased survey of Australian adults demonstrated that, compared to those with low psychological distress, adults with increased psychological distress have higher odds for insufficient weekly physical activity, insufficient daily fruit and vegetable intakes, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these individuals are more likely to exhibit recommended health behaviors, given that the morbidity of mental illness may be reduced compared to that for patients of mental health services. Importantly though, we have recently demonstrated that such populations demonstrate similarly increased prevalence of several noncommunicable diseases such as coronary heart disease, diabetes, and respiratory disorders to that observed in studies of psychiatric patients, 7 suggesting that the poor health behaviors that contribute to these disorders may be similarly prevalent in the general population with mental illness. The aim of this populationbased survey of Australian adults was to compare health behaviors among participants with and without a mental illness.…”
mentioning
confidence: 92%